Educational Consumership and Tomorrow's Schools - John R. Dettre (Educational Considerations, 1973)
Unless those who hold that schools have value identify more effective ways of getting the best ideas into practice in the least wasteful time, the chances are that schools will not change at all, warns this thoughtful essayist. Every concerned educator, he suggests, must develop "the necessary skills and understandings to operate as a skilled consumer of proposed ideas for change in education." He offers practical guidelines.